Selective Breeding Approach to Study the Nauplii Size Variations in Artemia: Selective breeding of Artemia nauplii - P. A., Vikas; N.K. SAJESHKUMAR; P.C. THOMAS; SANIL N.K; JAYASANKAR; K.K. VIJAYAN (Fishery Technology, 2024)
Aquaculture plays a significant role in providing healthy protein and meeting food security for the marginalized communities. Aquaculture in most cases relies on hatchery-produced fish seeds. Hatchery seed production  success depends on the larval feeding, and presently most of the seed production commences with live feeds. Artemia is considered the universal live feed in aquaculture for its universal availability, easy storage, and nutritional advantages. The objective of the present study is to reduce the nauplii size by following the selective breeding approach using the cysts collected from the hypersaline habitats of Kelambakam (CKF), Southeast India. Nauplii length reduction was evident with a selection gain of -2.40 µm in G1, -9.86 µm in G2, and -10.70 µm in G4. The study reduced the nauplii length of Artemia by 14.9 percent from the 15-generation selective breeding approach using the Artemia strain collected from India. The study reports that the genetic effect on the nauplii length in response to the selection is significant. Cumulative selection gain of the mass selection was evident from the variance values. Nonadditive genetic factors also contributed substantially to the total genetic variance and are indicated by the higher h2 values. The increase in hatching percentage (10% increase) may be due to the cumulative effect of the selection. Live feed quality standards are defined regarding nutrient content, size, hatching percentage, etc. The selective breeding approach seems an ideal option for developing superior strains to replace the imported strains.